High RBM3 expression in prostate cancer independently predicts a reduced risk of biochemical recurrence and disease progression - Bjartell Anders; Uhlén Mathias; Ulmert David; Gaber Alexander; Jonsson Liv; Jirström Karin (BMC, 2011)
Abstract Background High expression of the RNA-binding protein RBM3 has previously been found to be associated with good prognosis in breast cancer, ovarian cancer, malignant melanoma and colorectal cancer. The aim of this study was to examine the prognostic impact of immunohistochemical RBM3 expression in prostate cancer. Findings Immunohistochemical RBM3 expression was examined in a tissue microarray with malignant and benign prostatic specimens from 88 patients treated with radical prostatectomy for localized disease. While rarely expressed in benign prostate gland epithelium, RBM3 was found to be up-regulated in prostate intraepithelial neoplasia and present in various fractions and intensities in invasive prostate cancer. High nuclear RBM3 expression was significantly associated with a prolonged time to biochemical recurrence (BCR) (HR 0.56, 95% CI: 0.34-0.93, p = 0.024) and clinical progression (HR 0.09, 95% CI: 0.01-0.71, p = 0.021). These associations remained significant in multivariate analysis, adjusted for preoperative PSA level in blood, pathological Gleason score and presence or absence of extracapsular extension, seminal vesicle invasion and positive surgical margin (HR 0.41, 95% CI: 0.19-0.89, p = 0.024 for BCR and HR 0.06, 95% CI: 0.01-0.50, p = 0.009 for clinical progression). Conclusion Our results demonstrate that high nuclear expression of RBM3 in prostate cancer is associated with a prolonged time to disease progression and, thus, a potential biomarker of favourable prognosis. The value of RBM3 for prognostication, treatment stratification and follow-up of prostate cancer patients should be further validated in larger studies.